1359-P: Diabetes Control and Complications in North India—Three-Year Results of LANDMARC Trial - MITHAL, AMBRISH; KUMAR WANGNOO, SUBHASH; ZARGAR, ABDUL H.; CHAWLA, RAJEEV; GUPTA, MUKULESH; MITTAL, VINOD; KHANDELWAL, DEEPAK; JULKA, SANDEEP; JINDAL, SUSHIL; LODHA, SAILESH; BANZAL, SUBODH S.; MENON, SHALINI K.; et al. (Diabetes (New York, N.Y.), 2024)
Glycemic control, therapy trends, and diabetes complications were evaluated in LANDMARC, a prospective observational 3-year study (CTRI/2017/05/008452), having participants with T2D on ≥2 antihyperglycemic medications. This subgroup analysis of 114 sites in North India (Delhi, Jaipur, Lucknow) included 1686 participants (mean [SD] baseline [BL] age: 51.7 [8.8] years, T2D duration: 8.7 [5.5] years and A1C: 8.1% [1.6]). At BL, most were insulin-naïve (n=1332; 79.0%), relying mainly on OADs (n=1324; 78.5%). At 3 years, 1028 (70.1%) participants were on OADs only, while 414 (28.2%) were on insulin + OADs. Biguanides was the most prescribed drug class (BL: 1558 [92.4%] and 3-years: 1313 [89.5%]). Basal insulin usage increased from BL (n=199; 11.8%) to 3 years (n=284; 19.4%). At 3 years, there was a decrease in the mean (SD) A1C by 0.8 (1.7) %, FPG by 17.0 (51.4) mg/dL, and PPG by 19.1 (79.0) mg/dL; and an increase in proportion of those with A1C<7% (BL: 257 [21.2%]; 3 years: 363 [38.6%]). Peripheral vascular disease and neuropathy were most common macrovascular and microvascular complications, respectively (Table). Hypertension and dyslipidemia were the most common CV risk factors reported at 3 years. The highest burden of hypertension was noted in North India. This pivotal understanding of regional trends in glycemia, therapy, and complications may help strategize future diabetes management practices in India.